Impairment of platelet NO signalling in coronary artery spasm: role of hydrogen sulphide. (23rd February 2021) - Imam, Hasan; Nguyen, Thanh H.; Stafford, Irene; Liu, Saifei; Heresztyn, Tamila; Chirkov, Yuliy Y.; Horowitz, John D.
Abstract : Background and Purpose: The pathophysiology of coronary artery spasm (CAS), with its associated ischaemic crises, is currently poorly understood and treatment is frequently ineffective. In view of increasing evidence that platelet‐based defects may occur in CAS patients, we investigated platelet reactivity in CAS patients and whether symptomatic crises reflect activation of platelet–endothelial interactions. Experimental Approach: CAS patients were evaluated during acute and/or chronic symptomatic phases and compared with healthy control subjects. Inhibition of ADP‐induced platelet aggregation by the NO donor sodium nitroprusside (SNP) and plasma concentrations of syndecan 1 (glycocalyx shedding marker), tryptase (mast cell activation marker) and platelet microparticles were measured. Key Results: Inhibition of platelet aggregation by SNP was diminished in chronic CAS, with further (non‐significant) deterioration during symptomatic crises, whereas plasma concentrations of syndecan 1, tryptase and platelet microparticles increased. Treatment of patients with high‐dose N ‐acetylcysteine (NAC) plus glyceryl trinitrate rapidly increased platelet responsiveness to SNP and decreased plasma syndecan 1 concentrations. The effect of NAC on platelet responsiveness to SNP was confirmed in vitro and mimicked by the H2 S donor NaHS. Conversely, inhibition of enzymatic production of H2 S attenuated NAC effect. Conclusion and Implications: CAS is associated with substantial impairment of platelet NO signalling. During acute symptomatic exacerbations, platelet resistance to NO is aggravated, together with mast cell activation and damage to both vasculature and platelets. NAC, via release of H2 S, reverses platelet resistance to NO and terminates glycocalyx shedding during symptomatic crises: This suggests that H2 S donors may correct the pathophysiological anomalies underlying CAS. Abstract :